Upaya Pencegahan Kehamilan pada Usia Remaja Melalui Edukasi di Posrem Droseros Danau Sipin Kota Jambi - Kusuma, Ratu (Universitas Baiturrahim, 2024)
Teenage pregnancies are a global problem, the 2018 Riskesdas Data recorded 2,867 teenage pregnancies (10-19 years) and 15 of them were aged 10-14 years. BPS Indonesia reports that the average teenage births in 2018 were 36/1000 births and in Provinsi Jambi 46/1000 births (national target 18/1000 births). One effort to reduce this number is to provide education. Therefore, the Baiturrahim STIKes team carried out community service activities at the Posrem Droseros Danau Sipin, the working area of the Puskesmas Putri Ayu, Kota Jambi. Based on the initial survey, it is known that there were 30 teenage pregnancies (16-19 years) from 01-31 August 2022 which were possibly caused by the large number of teenagers dropping out of school; feeling bored with the online learning system during the co-19 pandemic. Other factors are: drug use/history of drug use; free sex/premarital sex; unwed pregnancy; the presence of HIV-infected adolescents; economic factors; Not all teenagers actively participate in education and other activities. The series of activities started from September 2022 to February 2023 at the Rumah Tenun Disperindag Kota J which was attended by 22 teenagers (1 pregnant teenager, 1 post-abortion teenager, 2 teenage mothers). This activity was also attended by 2 posyandu cadres for pregnant women and toddlers, as well as 3 health workers from Puskesmas Putri Ayu. Material delivered via power point for 50-60 minutes. Before and after education, pretest and posttest were carried out using the same questionnaire. The results obtained were an average increase in knowledge of 1.5 and attitude of 3.4 points after being given education about efforts to prevent pregnancy in adolescents.